Battling COVID-19 Pandemic: Sphingosine-1-Phosphate Analogs as an Adjunctive Therapy? - Naz, Farha; Arish, Mohd (Frontiers in Immunology, 2020)
With the sudden outbreak of COVID-19 patient worldwide and associated mortality, it is critical to come up with an effective treatment against SARS-CoV-2. Studies suggest that mortality due to COVID 19 is mainly attributed to the hyper inflammatory response leading to cytokine storm and ARDS in infected patients. Sphingosine-1-phosphate receptor 1 (S1PR1) analogs, AAL-R and RP-002, have earlier provided in-vivo protection from the pathophysiological response during H1N1 influenza infection and improved mortality. Recently, it was shown that the treatment with sphingosine-1-phosphate receptor 1 analog, CYM5442, resulted in the significant dampening of the immune response upon H1N1 challenge in mice and improved survival of H1N1 infected mice in combination with an antiviral drug, oseltamivir. Hence, here we suggest to investigate the possible utility of using S1P analogs to treat COVID-19.